Artisan instruments in the teaching of physical geography in the 6th year of fundamental education - Araujo, Aline Gabriela Silveira; Molinari, Deivison Carvalho (Geosaberes; Vol 8 No 14 (2017): Jan - Apr, 2017)
The article presents methodological proposals to work on subjects related to Physical Geography in the classroom, aiming that this area of ​​geographic science be seen in a more accessible and related to the daily life of students. The work is the result of activities developed in the Institutional Scholarship Program for Scientific Initiation (PIBIC). The methodological procedures began with the bibliographical survey, followed by analysis of two didactic books and later the execution of the experiments and equipment on the subjects worked. It was thought of a didactic as well as a sustainable approach, since the handmade instruments were constructed with materials recycled and / or of easy access, like materials that the student owns in his domestic environment. The research proved that it is possible to work Physical Geography in an interesting and enjoyable way, bringing the content of the textbook to the reality of the students, making it possible for them to understand more clearly the natural dynamics of the geographic space.
Keywords: Geografia; Ensino; Geografia Física; Instrumentos Artesanais